Aspek-Aspek Hukum Adat Banjar dalam Kehidupan Bermasyarakat: Relevansi dan Penerapan - Nazifah Hanafiah (Integrated Education Journal, 2024)
This journal examines aspects of banjar customary law in social life, which is an integral part of the legal system in Indonesia, especially in South Kalimantan. Unwritten Banjar customary law reflects cultural values and traditions of the local community, and is rooted in social norms and Islamic teachings. Social norms and Islamic teachings. This research aims to explore the application of Banjar customary law in various aspects of life, including marriage, inheritance and conflict resolution. Through a qualitative research method that relies on literature sources, it is found that Banjar customary law is still relevant and respected in the modern context despite facing challenges from modernization and integration with state law. The results research shows that Banjar customary law functions as a moral and social guidelines that maintain harmony in society. Aspects such as marriage procedures that involve family deliberation, inheritance distribution that pays attention to sharia principles, as well as dispute resolution through customary mediation. sharia principles, as well as dispute resolution through customary mediation, reflect the values of justice and togetherness. However, challenges such as erosion of local culture and the influence of modernization threaten the sustainability of customary law. Therefore, it is important to understand the dynamics of Banjar customary law in the context of social change in order to maintain the cultural identity of the Banjar community in the midst of globalization.